2018
DOI: 10.1007/s00404-018-4881-7
|View full text |Cite
|
Sign up to set email alerts
|

Residual lesions in uterine specimens after loop electrosurgical excision procedure in patients with CIN

Abstract: Abnormal ECC result and post-treatment HPV infection are predictors of residual lesion after LEEP. In combination, they could be useful for risk stratification and selection of the management approach. Postmenopausal CIN2+ patients with positive margins and persistent postoperative HPV infection may have high risk of cervical invasive cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…These studies differ from each other methodologically, including the study populations and analysis of variables. However, similar to our results, studies found that ECC positivity 13,19,20 was a significant risk factor for residual disease. The finding that abnormal ECC results were independently associated with residual lesions in uterine specimens indicates the feasibility of identifying risk factors before conization and may be helpful in pre-procedural planning to optimize clinical management.…”
Section: Dovepresssupporting
confidence: 92%
See 2 more Smart Citations
“…These studies differ from each other methodologically, including the study populations and analysis of variables. However, similar to our results, studies found that ECC positivity 13,19,20 was a significant risk factor for residual disease. The finding that abnormal ECC results were independently associated with residual lesions in uterine specimens indicates the feasibility of identifying risk factors before conization and may be helpful in pre-procedural planning to optimize clinical management.…”
Section: Dovepresssupporting
confidence: 92%
“…Several previous studies have evaluated clinical and pathological predictors of the persistence of or residual CIN and cervical cancer. 3,[5][6][7][8][9][10][13][14][15][16][17] However, only a few studies have examined whole uterine specimens after hysterectomy 13 and have focused on post-menopausal patients alone. These studies differ from each other methodologically, including the study populations and analysis of variables.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of two previous studies are consistent with our findings to a certain degree, which is noteworthy for us. One is that Lin et al [14] found that an abnormal ECC result was an independent predictor of the risk of residual lesions. The other study reported a similar result regarding preoperative endocervical curettage, which was significantly associated with persistent or recurrent CIN [5].…”
Section: Discussionmentioning
confidence: 99%
“…③ The presence of residual uterine fibroids was determined by intracavitary color Doppler ultrasonography within 3 weeks after surgery. Diagnostic criteria [ 8 ]: postoperative ultrasonography showed solid hypoechoic nodules with diameter ≥1.0 cm and clear capsule. Patients were asked to go to the hospital for re-examination 3, 6, and 12 months after surgery.…”
Section: Methodsmentioning
confidence: 99%